Increased stromal PFKFB3-mediated glycolysis in inflammatory bowel disease contributes to intestinal inflammation - Zhou, Zhou; Plug, Leonie G.; Patente, Thiago A.; de Jonge-Muller, Eveline S. M.; Elmagd, Amir Abou; van der Meulen-de Jong, Andrea E.; Everts, Bart; Barnhoorn, Marieke C.; Hawinkels, Lukas J. A. C. (Frontiers in Immunology, 2022)
Inflammatory bowel disease (IBD) is a chronic relapsing inflammation of the intestinal tract with currently not well-understood pathogenesis. In addition to the involvement of immune cells, increasing studies show an important role for fibroblasts in the pathogenesis of IBD. Previous work showed that glycolysis is the preferred energy source for fibroblasts in fibrotic diseases. 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase 3 (PFKFB3) is a key kinase supporting glycolysis. Increased expression of PFKFB3 in several cancers and inflammatory diseases has been previously reported, but the metabolic status of fibroblasts and the role of PFKFB3 in patients with IBD are currently unknown. Therefore, in this study, we evaluated the role of glycolysis and PFKFB3 expression in IBD. Single-sample gene set enrichment analysis (ssGSEA) analysis revealed that glycolysis was significantly higher in IBD intestinal samples, compared to healthy controls, which was confirmed in the validation cohorts of IBD patients. Single cell sequencing data indicated that PFKFB3 expression was higher in IBD-derived stromal cells. In vitro, PFKFB3 expression in IBD-derived fibroblasts was increased after the stimulation with pro-inflammatory cytokines. Using seahorse real-time cell metabolic analysis, inflamed fibroblasts were shown to have a higher extracellular acidification rate and a lower oxygen consumption rate, which could be reversed by inhibition of JAK/STAT pathway. Furthermore, increased expression of pro-inflammatory cytokines and chemokines in fibroblasts could be reverted by PFK15, a specific inhibitor of PFKFB3. In vivo experiments showed that PFK15 reduced the severity of dextran sulfate sodium (DSS)- and T-cell transfer induced colitis, which was accompanied by a reduction in immune cell infiltration in the intestines. These findings suggest that increased stromal PFKFB3 expression contributes to inflammation and the pathological function of fibroblasts in IBD. Inhibition of PFKFB3 suppressed their inflammatory characteristics.